Impact of internal factors on product innovation: Empirical Evidence from Vietnamese textile and garment firms - Huong, Vu Thi Thu; Thanh, Nguyen Đac (International Journal of Innovative Research and Scientific Studies, 2024)
This article aims to examine the internal factors affecting product innovation in Vietnamese textile and garment enterprises. The study used statistical methods and logit regression models along with data collected from the 2021 Economic Census of the General Statistics Office of Vietnam. The research results show some statistically significant results, as follows: (i) enterprises with state capital account for the lowest proportion in the sample but have the highest product innovation rate, and the proportion of product innovation in textile and garment enterprises increases gradually with enterprise size; (ii) enterprise characteristics (employee size and import-export activities) have a positive influence on product innovation; (iii) characteristics of business owners including gender, level of expertise, and gender diversity among owners all influence product innovation; (iv) applying information technology (using the internet, management software, automation systems, and spending on software) has a positive influence on product innovation; (v) enterprise resources for innovation including capital intensity and research and development activities have a positive influence, while, labor costs have a negative influence on product innovation. Furthermore, the role of capital intensity in product innovation depends on the type of enterprise. Specifically, this influence is strongest for enterprises with 100% foreign capital but is not statistically significant for joint-stock companies that do not have state capital. The research results are the basis for proposing solutions and recommendations to increase the product innovation of textile and garment enterprises in Vietnam.